Evaluation of commercial methods to separate nucleic acids from intestinal tissues of pigs for diagnosis of porcine epidemic diarrhea - MasiukD. М.; Nedzvetsky, V. S.; Kokariev, A. V.; Danchuk, O. V.; Vasilenko, T. O.; Yefimova, O. M. (Regulatory Mechanisms in Biosystems, 2019)
The article presents the results of evaluating commercial methods for extracting nucleic acids from pig intestinal tissues for the diagnosis of PED. The study was based on samples of small intestine tissues and faeces from 3–5 day old pigs which died from PED. Nucleic acid extraction was performed using commercial kits with different nucleic acid separation strategies based on: silicon-sorbent; silicate membrane fixed in a microcentrifuge column and magnetic balls. The studies were conducted in two stages. The first was a comparison of the results of the amplification of the obtained nucleic acid extracts from the homogenate of the intestines of piglets by using the above-mentioned commercial kits for the extraction of nucleic acids. For this purpose, samples of homogenate were used which in weight corresponded to the guideline for the application of the test kits. The second step was directed to determining the efficiency of extraction of DNA and RNA from homogenate samples with a weight of 10, 50, 100 and 200 mg. Determination of the optimal methodological strategy of nucleic acid extraction for the diagnosis of porcine epidemic diarrhea by PCR has been investigated. The results of the PCR studies of RNA of the PED virus and a unique pig DNA fragment indicate that the extraction of nucleic acids by commercial kits has different levels of efficiency and depends on different factors. According to the research, it was found that the most important of them are the adsorption capacity of the solid-phase sorbent, its configuration and nature, which binds RNA and DNA molecules, the type of sample from which extraction takes place, its volume, or the tissue mass used for extraction. Based on the obtained results, it has been found that the most effective PED virus RNA extraction is by “ArtBioTech”, “Bio Extract Column”, and “Viral DNA/RNA Extraction Kit”, and pig genomic DNA extraction by the “ArtBioTech” and “Viral DNA / RNA extraction Kit”.